Empowerment and Well-Being Through Participatory Action Research and Accessible Gaming: A Case Study With Adults With Intellectual Disability - Sousa, Carla; Neves, José Carlos; Damásio, Manuel José (Frontiers in Education, 2022)
Although the potential of games to foster learning, representation, empowerment, well-being, and social inclusion is already documented, some groups seem to remain underrepresented. In the field of disability, this potential is still immersed in a set of barriers and hindrances, arising from the lack of accessibility of this medium and the lack of representation of voices in research and development processes. This problem seems to be exponentiated in the field of Intellectual Disability (ID). The present study describes insights from a case study developed with 14 institutionalized adults with severe ID, with two complementary aims: (a) explore the effectiveness of a PAR gaming approach in the empowerment and well-being of adults with ID living in an institutional setting; and (b) explore the feasibility of promoting accessibility in games through PAR. The proposed intervention included the development of games by higher education students for these individuals, with their active participation in all phases – conceptual definition, game design, game development, and playtesting. A total of 38 playtesting sessions and 162 gaming sessions were conducted, where systematic observation grids were filled, and pre and post-process assessments were conducted, targeting variables related to empowerment and well-being. The obtained results sustain this type of action-research design as a feasible strategy to empower people with ID and foster their well-being, through games as a form of expression and not only therapy. It also reflects on accessibility improvement through the presence of underrepresented groups (people with ID particularly) in the media creation processes that can, per se, be considered a form of empowerment. These insights also open a discussion about a potential paradigm shift toward a social model of accessibility aligned with the current views on the field of disability studies. Future studies should replicate this methodology with larger samples and in a context not aligned with the pandemic isolation. Furthermore, PAR must also be explored from a more general perspective, as a strategy to promote accessibility and participation in other media and cultural products as a whole.